THE TYPES OF FLOUTING MAXIM IN THE MAIN CHARACTER'S UTTERANCES OF OCEAN'S 8 MOVIE - Kadek Ayu Dwina Wahyuni Wina (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study aims to identify the types of flouting maxim that were flouted in Ocean’s 8 movie by the main character. This study was focused on analyzing the types of flouting maxim that were flouted by the main character of the movie. This study used Grice (1975) theory as the theory of the types of flouting maxim. This study used descriptive qualitative method in analyzing the data. The data were collected by downloading the Ocean’s 8 movie, watching the movie, and taking a note the conversation that contain flouting maxim. The finding of this study showed three types of flouting maxims were flouted by the main character in the movie. The finding showed that the maxims were flouted 10 times. The most dominant flouting maxim that uttered by the main character of the movie is flouting maxim of quality that is occurred 5 times (50%).